Warriors of Imperial Japan in World War II 1941-45 (2601-05) - Antonucci, Claudio ([Concord color series] ;)
In terms of books dedicated to Axis forces during WWII, Germany consumes more than the lion's share of literature. Alas, there is little devoted to the fascinating subject of the Japanese soldier during this global conflict.